Tema: incentivos fiscais: uma visão a partir do constructivismo lógico-semântico - Piva, Sílvia Helena Gomes (2014)
This thesis analyzes tax incentives under the regulation point of view and based on logical-semantic constructivism. The starting point is the analysis of the lack of consensus surrounding the term tax incentives and the wastage in the use of it by the doctrine. The main studies related to tax incentives already produced were analyzed, as well as the absence of systemic organization of the rules dealing with tax incentives at the constitutional and infraconstitutional levels. The analysis of tax incentives that are presented in this work is based on logical semantic constructivism, which brings a new point of view on the subject. Whereas most tax incentives related analysis takes into consideration the tax object, the view presented here differs from previous studies by seeking a review of its regulatory framework. Understanding tax incentives in a linguistic study allows adding a richer view on previous work already developed on the matter, because it intersects this pragmatic load other studies undertaken by the two semiotic instances syntactic and semantic to allow a full view of the legal phenomenon. Thus an attempt was made to remove the vague and ambiguous sense of the term tax incentives and relocate it according to its legal regime of taxes, according to a classification of the analysis of legal rules and their respective interference in matrix rule of tax incidence. In this way, the analysis of tax incentives on a constitutional perspective was carried out to find its validity, limitations and motivations of constitutional order, so that the constitutional principles underlying the tax incentives were analyzed. From a normative perspective for fiscal incentives, the standard structural fiscal stimulus was built, and it starts from a standard of competence outlined in the Constitution. The identification about tax incentives being true legal rules was created and it acts upon a set of rules that interfere with the matrix rule of tax incidence. Thus, the rules that do not interfere with the matrix rule of tax incidence can be regarded as a tax incentive. The work was finished with the analysis of the constitutionality of illegitimate tax incentives and the mechanisms that the constitutional system has to flush the rules that grant incentives erratically while honoring the constitutional principles that protect the relationship between tax authorities and taxpayers